Impact of summer monsoon on the elevation‐dependence of meteorological variables in the south of central Himalaya. (22nd September 2017) - Yang, Kun; Guyennon, Nicolas; Ouyang, Lin; Tian, Lide; Tartari, Gianni; Salerno, Franco
ABSTRACT: The South Asian summer monsoon brings abundant precipitation and associated latent heat release to the south of central Himalaya, and alters hydrothermal conditions of this region. This study explored the impact of South Asian summer monsoon on the elevation‐dependence of meteorological variables along the south slope of Mt. Everest in the central Himalaya, which is crucial to modelling the glacio‐hydrological processes in this elevated region. The data were collected at five stations deployed at 2660–5600 m above sea level (asl) along the slope during 2007–2011. Major findings are the following: (1) The amount of precipitation during the monsoon season usually decreases with elevation but it is relatively uniform between 3600 and 5000 m asl. This uniform profile may be attributed to the monsoon–terrain–land interactions, particularly to the retard effect of glacier cooling on daytime upvalley wind; (2) Cloud shielding effects cause lower solar radiation and higher downward longwave radiation in the monsoon than in the other seasons. In particular, higher elevations have more clouds in the afternoon, resulting in an abnormal elevation‐dependence of solar radiation (i.e. higher elevations receive less solar radiation); (3) Strong daytime upvalley wind and moist convection homogenizes the vertical distributions of air mass along the slope, causing a constant lapse rate of both surface air temperature and dew‐point temperature (representing humidity) during typical monsoon months, but this phenomenon is not found in the other seasons. These findings provide critical guidance for extrapolating the meteorological variables from lower to higher elevations in this region. Abstract : South Asian summer monsoon greatly affects the elevation‐dependence of meteorological variables along the steepest valley in the world (south of Mt. Everest). Strong daytime upvalley winds and deep convection during the monsoon season cause a uniform precipitation profile between 3500 and 5000 m above sea level, an abnormal elevation‐dependence of solar radiation (higher elevations receive less solar radiation), and a constant vertical gradient of near‐surface air temperature and dew‐point temperature.